SETTLEMENT PATTERN MODEL AT RIVERSIDE (A Case Study of Martapura River) - Nurfansyah Nurfansyah (INFO-TEKNIK, 2008)
The Martapura River is the watercourse fromBaritoRiver. Cultural of the ordinary society that used to life around the riverside caused to expand the settlement along the riverside.This research purposed synthesis the settlement characteristics along riverside and make the settlement model. The methods used at this research was rationalistic, where the research object consisted of three village and analysis based on research parameters, settlement pattern, form, circulation and infrastructure.The result of this research are linear settlement pattern expand along the riversideMartapuraRiverunorganized. At the curve area, there is cluster settlement pattern where the building grown from the main road to the riverside. There are pillar house and floating house that have grown at some spots along the riverside and alley are the circulation of the area where both interconnected. Wooden bridge represent to access of the circulation. The area infrastructure consisted of floating MCK. The MCK was a communal place for the riverside society doing activity, bath, cleaning and wasting. The floating MCK also used as dock by river transportation passenger. Domestic waste a lot still thrown to the river and not places for temporary waste place so the river become dirty by the garbage.